Analisis Pemilihan Pemasok Coating Oil Menggunakan Metode Fuzzy AHP Studi Kasus : PT. Petrokimia Gresik - Muhammad Iqtada Aliyyuddin Hanif; Hammam Muhammad Afiq; Novi Marlyana; Nurwidiana Nurwidiana (CV. KAMPUS AKADEMIK PUBLISING, 2025)
PT Petrokimia Gresik, as one of the largest fertilizer producers in Indonesia, faces serious constraints regarding the quality and timeliness of coating oil raw material deliveries. Inconsistent supply from several suppliers impacts the quality of the final product and the production process. Therefore, selecting the right supplier is crucial and must be done systematically. This research uses the Fuzzy Analytic Hierarchy Process (Fuzzy AHP) method, a multi-criteria decision-making method capable of accommodating uncertainty and subjectivity in assessments. Using this method, all supplier selection criteria are evaluated comprehensively to determine the best alternative. The final result shows that PT B is the most optimal choice with the highest preference value. In its efforts to maintain the production of quality fertilizer, PT Petrokimia Gresik faces a significant challenge stemming from a fertilizer coating raw material: coating oil. The main issues arise from inconsistent product quality and delivery delays from several suppliers, which impact operational efficiency and have the potential to disrupt the production process. Consequently, the company requires an evaluation approach that is not only rational but also capable of encapsulating the complexity and uncertainty in the decision-making process. This research employs the Fuzzy Analytical Hierarchy Process (Fuzzy AHP) method as a tool to assess and determine the best supplier based on a number of strategic criteria. Fuzzy AHP was chosen due to its advantage in capturing subjective perceptions and converting them into more measurable and accurate quantitative data. Through this approach, all supplier alternatives were systematically compared based on six main criteria and 17 sub-criteria. The final results indicate that PT B is the most superior alternative, based on the highest preference score and consistent performance in aspects of quality and timeliness.